Fundamentals of oral and maxillofacial radiology - Hubar, J. Sean 1954- (Fundamentals (Dentistry) Ser., 2017)
Fundamentals of Oral and Maxillofacial Radiology provides a concise overview of the principles of dental radiology, emphasizing their application to clinical practice.-Distills foundational knowledge on oral radiology in an accessible guide -Uses a succinct, easy-to-follow approach -Focuses on practical applications for radiology information and techniques -Presents summaries of the most common osseous pathologic lesions and dental anomalies -Includes companion website with figures from the book in PowerPoint and x-ray puzzles.- Resumé vydavatel